Reflections on the pedagogical practice in outdoor/indoor soccer schools for children based on the reading and compreension of specific contexts - Rezer, Ricardo; Shigunov, Viktor (Journal of Physical Education (Maringá), 2008)
The purpose of this study is to investigate the pedagogical practice in the outdoor/indoor soccer schools for children, pointing out the guiding principles of methodological procedures which can serve as overcoming presuppositions. This is a descriptive-exploratory study carried out at 02 outdoor soccer schools for children and 04 indoor soccer schools for to 6-8-year-old and 9-10-year-old categories. The following instruments were used: Profile Survey; Semi-structured Interview; Observation and Registry of the classes. The reflections suggest that the outdoor and indoor soccer teaching contexts need to realize the sports under a wider perspective of understanding. This study intended to open “new views”, contributing to the outdoor/indoor soccer teaching-learning process, based on a differential action and reflection perspective.